2009
DOI: 10.1144/sp321.7
|View full text |Cite
|
Sign up to set email alerts
|

Timing and nature of formation of the Ios metamorphic core complex, southern Cyclades, Greece

Abstract: We apply low-temperature thermochronology, Rb/Sr geochronology, petrological data, and structural mapping to constrain the timing and kinematics of the Ios metamorphic core complex. Top-to-north extension in the lower plate Headland Shear Zone was active at 18-19 Ma under metamorphic conditions of 475-610 8C and 0.65-1.1 GPa. The South Cyclades Shear Zone/Ios Detachment Fault (SCSZ/IDF) system shows top-to-south extensional shear active at c. 19 Ma at 380-550 8C, with local top-to-north bands. Extensional shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(97 citation statements)
references
References 107 publications
(188 reference statements)
4
93
0
Order By: Relevance
“…Because the top-tothe-south structures of the Sifnos Detachment largely formed in the brittle crust, the onset of deformation on the Sifnos Detachment probably did not commence long before the oldest ZFT ages of c. 13 Ma. Such an inference is corroborated by detailed work on other detachments in the Aegean Sea region, which showed that these detachments are rather short-lived structures that operated over c. 5-10 Ma (Gessner et al 2001;Ring et al , 2007bBrichau et al 2006Brichau et al , 2007Brichau et al , 2008Brichau et al , 2010Thomson & Ring 2006;Thomson et al 2009). …”
Section: Sifnos Detachment and High-angle Normal Faultingmentioning
confidence: 68%
See 3 more Smart Citations
“…Because the top-tothe-south structures of the Sifnos Detachment largely formed in the brittle crust, the onset of deformation on the Sifnos Detachment probably did not commence long before the oldest ZFT ages of c. 13 Ma. Such an inference is corroborated by detailed work on other detachments in the Aegean Sea region, which showed that these detachments are rather short-lived structures that operated over c. 5-10 Ma (Gessner et al 2001;Ring et al , 2007bBrichau et al 2006Brichau et al , 2007Brichau et al , 2008Brichau et al , 2010Thomson & Ring 2006;Thomson et al 2009). …”
Section: Sifnos Detachment and High-angle Normal Faultingmentioning
confidence: 68%
“…1). Research over the last two decades has demonstrated the importance of Miocene low-angle extensional detachments in the formation of the Cyclades horst (Lister et al 1984;Avigad & Garfunkel 1989;Buick 1991;Brichau et al 2006;Thomson et al 2009;Jolivet & Brun 2010;. The detachments are top-to-the-north displacing at the northern end of the Cyclades (Evia, Andros, Tinos, Mykonos, Ikaria, Samos) (Avigad & Garfunkel 1991;Lee & Lister 1992;Kumerics et al 2005;Brichau et al 2007Brichau et al , 2008Mehl et al 2005 referred to a large part of these extensional faults as the North Cycladic Detachment System.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Metamorphic core complexes have been documented in areas marked by crustal extension interpreted as the result of gravitational collapse of a previously thickened crust (Brun, 1999;Buck, 1991;Corti et al, 2003;Jolivet et al, 2013). Their occurrence has been discussed for the North American Cordillera (e.g., Cubley et al, 2013a,b;Dallmeyer et al, 1986;Dokka et al, 1986;Kruckenberg et al, 2008;Norlander et al, 2002;Rey et al, 2009;Vanderhaeghe et al, 2003;Whitney et al, 2013), the eastern Mediterranean (Cyclades, western Turkey-Aegean) (Thomson et al, 2009;Dilek and Altunkaynak, 2009;Le Pourhiet et al, 2012;Jolivet et al, 2013), the Variscan Orogen of Europe (Augier et al, 2015;Brown and Dallmeyer, 1996;Ledru et al, 2001), and the central part of eastern Asia (Charles et al, 2012; Daoudene et al, 2013). Results of thermo-mechanical modeling of the evolution of many metamorphic core complexes show very rapid cooling after near-isothermal decompression under peak temperature conditions (e.g., Le Pourhiet et al, 2012;Rey et al, 2009).…”
Section: Tectonically-induced Coolingmentioning
confidence: 99%